IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. SARIWIGUNA BINASENTOSA, THROUGH THE BROILER CHICKEN CULTIVATION PROGRAM, TO IMPROVE CAPACITY BUILDING AND COMMUNITY WELFARE IN SAMPIK BACKWOODS, AIR BARA VILLAGE - Umi Hapsari; Badi’atun Nihayah; Jamilullah Jamilullah; Yessi Nirmala; Dede Sanjaya; Dedi Setiawan (Yayasan Education and Social Center, 2023)
One of the concrete steps for change to contribute to the society and environment where the company locates is through the Corporate Social Responsibility (CSR) program. The CSR program aims to improve the company's good name, maintain good relations between the company and stakeholders, help with problems in the surrounding environment, and improve community welfare. PT. Sariwiguna Binasentosa is a tin smelting, processing, and marketing company spread across several areas in Bangka Belitung Islands, one of which is in Air Bara Village. This type of CSR program conducts in Sampik backwoods, Air Bara Village. It is through community empowerment for broiler chicken farming. The selection of program activity type is where broiler chickens are economical livestock compared to other livestock. In addition, the growth is fast, and meat production is relatively short is 5-7 weeks. However, there are some drawbacks of this broiler cultivation or livestock, such that they are susceptible to disease, easily stressed, and selling prices are relatively fluctuating. The success of broiler farming is seeable from various aspects, including feed, body weight, etc. The results of cultivating twice the period showed a decrease in the mortality rate of chickens by 2.17%. In the first period, the death rate was 7.77% (39 of the 502-population died). While in the second period, the mortality rate was 5.60% (28 of the 500 population). The group succeeded in reducing the death rate of chickens by controlling the causal factors